2019
DOI: 10.2147/copd.s182015
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparative analysis of medical expenditure with nebulized budesonide versus systemic corticosteroids in hospitalized patients with acute exacerbations of chronic obstructive pulmonary disease in China</p>

Abstract: Purpose: Chronic obstructive pulmonary disease (COPD) is characterized by persistent respiratory symptoms and is a leading cause of disability in China. Acute exacerbations of COPD (AECOPD) are a leading cause of hospitalizations, and account for a substantial proportion of medical expenditure. Corticosteroids are commonly used to manage AECOPD in hospitalized patients, so our objective was to analyze the total medical expenditure associated with nebulized budesonide (nBUD) vs. systemic corticostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…This research found a link between the more significant reported burden of COPD (breathlessness, symptoms, and comorbidities) and higher overall societal expenses per patient [ 26 , 59 , 77 , 78 ]. Thus, the severity of the disease and symptoms might be one of the factors that influence the economic burden of COPD.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This research found a link between the more significant reported burden of COPD (breathlessness, symptoms, and comorbidities) and higher overall societal expenses per patient [ 26 , 59 , 77 , 78 ]. Thus, the severity of the disease and symptoms might be one of the factors that influence the economic burden of COPD.…”
Section: Discussionmentioning
confidence: 94%
“…In terms of components of the nonmedical direct cost, we discovered differences between studies. There were also cost-effectiveness studies; therefore, there were differences in treatment techniques [ 26 , 47 ]. Results showed that, direct costs are much higher in developed countries than in developing countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute exacerbations of COPD (AECOPD) can cause a significant decrease in lung function of patients and seriously affect the health and life of patients. It is the main reason for the hospitalization and death of COPD patients and places a heavy burden on the patient's family and the medical system (6,7). Therefore, AECOPD has been the focus of research in respiratory diseases in recent years (8)(9)(10)(11)(12).…”
Section: Original Articlementioning
confidence: 99%
“…[17][18][19][20] Recently, clinical studies and Metaanalysis have shown that nebulized budesonide (NB) is as effective as systemic corticosteroids in controlling nonacidotic AECOPD, as evaluated by clinical symptoms, lung function, and blood gas analysis. Furthermore, NB treatment reduces side effects [17][18][19][20][21][22] and medicine costs 23 compared to systemic corticosteroids. GOLD guidelines suggest NB as a suitable alternative to systemic corticosteroids in the treatment of exacerbations in some patients.…”
Section: Introductionmentioning
confidence: 99%